Montmorillonite solid superacid for flame retardance and preparation method thereof
By forming a super acid structure with B acid center in montmorillonite, the uneven distribution problem of SO42-loaded in montmorillonite is solved, and the efficient flame retardant effect is achieved, which significantly improves the unsaturated polyester resin. Flame retardant and thermal stability.
Patent Information
- Application Number
- CN202411383975.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-17
AI Technical Summary
The existing solid superacids loaded with SO42- in montmorillonite are unevenly distributed in polymer materials, resulting in low flame retardant efficiency and weak synergistic effects with phosphorus-based flame retardant, making it difficult to effectively improve the flame retardant properties of unsaturated polyester resins. .
By combining metal atoms M (such as Ti, Zr, Sn, Fe) with the montmorillonite skeleton and interlayer to form M-O-Si bonds and S-O-M bonds, a montmorillonite solid superacid with B acid center is prepared to achieve its polymerization in the polymerization process. Even distribution and efficient flame retardant in the object.
It significantly improves the flame retardant efficiency of unsaturated polyester resin, reduces the smoke release amount and rate during combustion, improves the thermal stability and residual carbon amount of the material, and has the best effect when using the phosphorus-based flame retardant APP.
Smart Images

Figure CN119144051A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardancy, in particular to a flame retardant montmorillonite solid super acid and a preparation method thereof. Background Art
[0002] Unsaturated polyester resin is widely used due to its excellent performance, but as a polymer material, flammability is a common problem, and it also releases toxic gases, which is harmful to the environment. Therefore, it is necessary to improve the flame retardancy of polymer materials. The addition of traditional phosphorus-based flame retardant APP can improve the flame retardancy of unsaturated polyester resin, but the phosphorus-based flame retardant APP is inefficient when used alone and the addition amount is large. It will also increase the amount of smoke released and the smoke release rate when UPR is burned, and the smoke release of flame retardant materials is an important indicator for evaluating fire hazards.
[0003] Existing literature such as CN116020425A, CN105457684B, etc. use montmorillonite to load SO4 2- , a solid superacid is obtained, the lamellar structure of montmorillonite and SO4 2- They mainly interact with each other through hydrogen bonds, which may cause the following problems: SO4 2- It is unevenly distributed in the lamellar structure of montmorillonite, and the hydrogen bond is unstable and easily replaced or falls off. If it is added to unsaturated polyester resin materials as a flame retardant synergist, it is easy to have weak synergy with APP, low flame retardant efficiency, and hydrogen bond breakage during resin curing or application, which will reduce the thermal stability of the material and limit the application field of the material. Summary of the invention
[0004] The present invention provides a montmorillonite solid superacid for flame retardancy and a preparation method thereof, and utilizes the skeleton and interlayer of MMT as a "cage" to encapsulate and anchor the superacid ligand to achieve its uniform spatial distribution and atomic-level dispersion, and prepares the montmorillonite solid superacid with a B acid center, which can be used for flame retardant synergy, improve flame retardant efficiency, and solve the problems of low efficiency of phosphorus-based flame retardant APP and large amount of smoke generated by burning of flame retardant UPR.
[0005] The technical solution of the present invention is achieved as follows: a flame retardant montmorillonite solid superacid, using the montmorillonite skeleton and interlayer as a cage to encapsulate and anchor the superacid ligand, the superacid ligand is a metal atom M, and a MO-Si bond is formed between the metal atom M and the montmorillonite skeleton or interlayer, and the metal atom M also binds to SO4 2- Through SOM bond coordination, a B acid center is formed.
[0006] Furthermore, the metal atom M is Ti, Zr, Sn or Fe.
[0007] A method for preparing a flame-retardant montmorillonite solid superacid comprises the following steps:
[0008] (1) calcining the metal ion cross-linked montmorillonite at 700-900° C. for 1-3 h to obtain metal atom pillared montmorillonite;
[0009] (2) immersing the metal atom pillared montmorillonite in a sulfuric acid solution, allowing it to stand, filtering and drying it to obtain a dried product;
[0010] (3) calcining the dried product at 400-600° C. for 3-5 h to obtain montmorillonite solid superacid.
[0011] Furthermore, the metal ion cross-linked montmorillonite in step (1) is titanium cross-linked montmorillonite, zirconium cross-linked montmorillonite, tin cross-linked montmorillonite or iron cross-linked montmorillonite.
[0012] Further, the preparation method of titanium cross-linked montmorillonite is as follows: under stirring conditions, 5-7 ml of Ti(C4H9O)4 is added dropwise to 3-5 ml of concentrated hydrochloric acid, and the mixture is stirred for 20-40 minutes, and then the mixture is allowed to stand at room temperature for 2-4 hours under sealed conditions to obtain a titanium cross-linking agent;
[0013] Under stirring conditions, a titanium crosslinking agent is added to a sodium-based montmorillonite suspension, and the mixture is stirred for reaction for 2-4 hours. After standing, the mixture is centrifuged, filtered, dried, and ground to obtain titanium crosslinked montmorillonite.
[0014] Further, the preparation method of zirconium cross-linked montmorillonite is as follows: 0.5-1.5 ml of concentrated hydrochloric acid, 35-40 ml of distilled water and 1-2 g of ZrOCl2 powder are mixed, magnetically stirred for 20-40 min, and allowed to stand for 2-4 h to obtain a zirconium cross-linking agent;
[0015] The zirconium crosslinking agent is added to the sodium montmorillonite suspension, stirred for reaction for 2-4 hours, allowed to stand overnight, centrifuged, filtered, dried, ground, and finally calcined at 450-550° C. for 2-4 hours to obtain zirconium crosslinked montmorillonite.
[0016] Further, the preparation method of the sodium-montmorillonite suspension is as follows: 1 g of sodium-montmorillonite (Na-MMT), 100 ml of acetone and 40 ml of deionized water are mixed to obtain a sodium-montmorillonite suspension;
[0017] Furthermore, in step (2), the concentration of the sulfuric acid solution is 1 mol / L, and the solvent of the sulfuric acid solution is water.
[0018] Furthermore, the mass percentage of concentrated hydrochloric acid is 36-37%.
[0019] Beneficial effects of the present invention:
[0020] After the titanium cross-linked montmorillonite of the present invention is calcined, the interlayers of the titanium cross-linked montmorillonite [(TiO) x (OH)y (H2O) z ] n+ The ions are transformed into TiO2 columns, and at the same time, the TiO2 columns form stable Ti-O-Si bonds with the montmorillonite crystal layers, making its structure more stable; then, SO4 2- The metal atoms are transformed into superacid ligands through SOM bond coordination on the surface of MMT, and strong B acid centers are generated. The skeleton and interlayer of MMT are used as "cages" to encapsulate and anchor the superacid ligands, achieving uniform spatial distribution and atomic-level dispersion, and preparing montmorillonite solid superacid with B acid centers. Other ion-crosslinked montmorillonites can also achieve the same effect after calcination.
[0021] The montmorillonite solid superacid prepared by the present invention can be used for flame retardancy. It is compounded with a traditional phosphorus flame retardant APP to perform flame retardant modification on unsaturated polyester resin (UPR). When the addition amount of the montmorillonite solid superacid is 0.1%, the APP and TiO2 / SO4 2— -PILCs have the best synergistic flame retardant effect, UPR / APP / TiO2 / SO4 2— -The LOI value of the PILCs synergistic flame retardant system reached 28.9%, which was 8.7% higher than that of pure UPR and 3.1% higher than that of the sample with 17% APP added; in addition, the CO, CO2, TSR, SPR, HRR, and THR released during combustion will decrease as the reaction proceeds, and the thermal stability and residual carbon content will also be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 The XRD comparison spectra of montmorillonite and cross-linked montmorillonite;
[0024] Figure 2 TiO2 / SO4 2- -XRD comparison spectra of PILCs and Ti-PILCs;
[0025] Figure 3 ZrO2 / SO4 2- -Comparison of XRD spectra of PILCs and Zr-PILCs;
[0026] Figure 4 TiO2 / SO42- -TEM images of PILCs;
[0027] Figure 5 ZrO2 / SO4 2— TEM images of PILCs;
[0028] Figure 6 is the amount of carbon dioxide released;
[0029] Figure 7 is the carbon monoxide release;
[0030] Figure 8 is the total amount of smoke released;
[0031] Fig. 9 is the smoke release rate;
[0032] Fig.10 is the total amount of heat released;
[0033] Fig.11 is the heat release rate;
[0034] Fig.12 is the TG curve;
[0035] Fig.13 is the DTG curve;
[0036] Fig.14 This is the molecular structure diagram of montmorillonite solid superacid. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] A method for preparing a flame-retardant montmorillonite solid superacid comprises the following steps:
[0040] (1) Weigh 1 g of sodium montmorillonite (Na-MMT) using an electronic balance, add 100 ml of acetone and 40 ml of deionized water to prepare a Na-MMT suspension with a mass concentration of 0.83%, and let it stand for use;
[0041] While stirring with a magnetic force at 350 rpm, take 6.80 ml of Ti(C4H9O)4 and add it dropwise to 3.4 ml of 37% HCl solution. Continue stirring for 30 minutes, cover with plastic wrap, and let stand at room temperature for 3 hours to obtain the Ti crosslinking agent for standby use.
[0042] Under the condition of magnetic stirring at 600 rpm, the Ti crosslinking agent was slowly added to the prepared Na-MMT suspension, the stirring was stopped after the reaction for 3 hours, the suspension was allowed to stand overnight, the suspension was centrifuged at 3800 rpm for 10 minutes, the suspension was filtered, the suspension was washed three times with distilled water, the suspension was dried in an oven, and the suspension was ground and sieved (200 meshes) to obtain Ti crosslinked montmorillonite (abbreviated as: TI-PILCs);
[0043] The Ti-crosslinked montmorillonite was placed in a muffle furnace and calcined at 800°C for 2 hours. During calcination, complex chemical changes occurred between the montmorillonite layers. The following reactions occurred in Ti-PILCs during calcination:
[0044] [(TiO) x (OH) y (H2O) z ] n+ →TiO2+H2O+H +
[0045] That is, after calcination, titanium cross-links the montmorillonite interlayers [(TiO) x (OH) y (H2O) z ] n+ The ions are transformed into TiO2 pillars, and stable Ti-O-Si bonds are formed between the pillars and the montmorillonite crystal layers, making its structure more stable, and Ti-pillared montmorillonite is obtained;
[0046] (2) soaking the Ti-pillared montmorillonite in 1 mol / L sulfuric acid, leaving it to stand for 24 hours, then filtering and drying it to obtain a dried product;
[0047] (3) The dried product was activated at 500°C for 4 h to obtain montmorillonite solid superacid (TiO2 / SO4 2- -PILCs).
[0048] like Fig.14 As shown in the figure, Ti cross-linked montmorillonite is calcined to become Ti pillared montmorillonite, and Ti pillared montmorillonite is acid leached and activated to become montmorillonite solid super acid, SSA is TiO2 / SO4 2- . Through acid leaching and activation, SO4 2- The metal atoms are transformed into superacid ligands through SOM bond coordination on the MMT surface and strong B acid centers are generated. The skeleton and interlayer of MMT are used as "cages" to encapsulate and anchor the superacid ligands to achieve uniform spatial distribution and atomic-level dispersion, thereby preparing montmorillonite solid superacid with B acid centers.
[0049] Example 2
[0050] This embodiment is basically the same as embodiment 1, except that: in step (1), 1.5 g of ZrOCl2 powder is measured using an electronic balance, put into a beaker, and then 1 ml of 37% hydrochloric acid and 36.5 ml of distilled water are added, magnetically stirred for 30 minutes, and allowed to stand for 3 hours to obtain a zirconium crosslinking agent. The prepared zirconium crosslinking agent is slowly added to the pre-prepared Na-MMT suspension and magnetically stirred for 3 hours, allowed to stand overnight, centrifuged at 3600 rpm for 10 minutes, filtered, washed, dried, and ground into 200 mesh particles, and calcined at 500° C. in a muffle furnace for 3 hours to obtain Zr crosslinked montmorillonite (Zr-PILCs).
[0051] The Zr-crosslinked montmorillonite was placed in a muffle furnace and calcined at 800°C for 2 h to obtain the Zr-pillared montmorillonite.
[0052] (2) soaking the Zr-pillared montmorillonite in 1 mol / L sulfuric acid, leaving it to stand for 24 hours, then filtering and drying to obtain a dried product;
[0053] (3) The dried product was activated at 500°C for 4 h to obtain montmorillonite solid superacid (ZrO2 / SO4 2- -PILCs).
[0054] TiO2 / SO4 2- -PILCs / UPR and ZrO2 / SO4 2- -Preparation of PILCs / UPR composites
[0055] Weigh 47g of 196 unsaturated resin, pour it into a beaker, add accelerator cobalt isooctanoate and curing agent methyl ethyl ketone peroxide (MEKP), stir evenly, pour into a mold and let stand to cure, and then pure UPR-0 is obtained. Mix the unsaturated resin and APP and pour them into a beaker. Ultrasonicate for 30 minutes to evenly disperse the APP, then add the accelerator and curing agent, mix evenly, pour into a mold and cure, and then UPR-1 is obtained. Unsaturated resin, APP, sodium montmorillonite, TiO2 / SO4 2— PILCs / UPR and ZrO2 / SO4 2- The PILCs / UPR mixture was poured into a beaker, and after ultrasonic treatment for 30 minutes, an accelerator and a curing agent were added, the mixture was evenly poured into a mold, and cured to obtain UPR-7, UPR-8 and UPR-9.
[0056] The sample formula is shown in Table 1 below
[0057]
[0058]
[0059] like Figure 1As shown in the figure, Na-MMT and Zr-PILCs both have characteristic peaks at 2θ=5°, 2θ=19° and 2θ=26°, but the peak values have changed, indicating that the introduction of Zr 4+ Later, the interplanar spacing of montmorillonite decreases. Figure 2 and Figure 3 Compared with Zr-PILCs, ZrO2 / SO4 2- -PILCs characteristic peak disappears at 2θ=5°, while TiO2 / SO4 2- Compared with the raw material Ti-PILCs, -PILCs show characteristic peaks at 2θ=19°, 2θ=25° and 2θ=26°.
[0060] like Figure 4 and 5 As shown, montmorillonite solid superacid has a lamellar structure, and the colors of the lamellar layers are dark and light. This is because the atomic density is different. The darker color is due to the formation of a superacid structure, and the atoms such as S, O, and Ti are concentrated together to make the color darker.
[0061] Table 2 UPR samples and limiting oxygen index
[0062] sample UPR-0 UPR-1 UPR-2 UPR-3 UPR-4 UPR-5 UPR-6 UPR-7 UPR-8 UPR-9 LOI(%) 20.1 23.8 24.5 24.8 25.2 25.5 25.8 26.1 28.9 28.5
[0063] It can be seen from Table 2 that with the increase of APP addition, the LOI of the sample also increases. When the APP content reaches 17%, the LOI of UPR-6 is 25.8%. After adding Na-MMT synergist, the oxygen index of the sample only increases by 0.3%; after adding montmorillonite solid superacid synergist, the oxygen index increases by 3.1% and 2.7% respectively, and the flame retardant synergistic effect is significantly improved. When the oxygen index is >27, it belongs to the flame retardant material, which can prove that TiO2 / SO4 2- -PILCs and ZrO2 / SO4 2- -PILCs and APP have good synergistic flame retardant effect.
[0064] like Figure 6 As shown, the carbon dioxide release of the pure UPR sample was the highest. After adding 17% APP, the carbon dioxide release decreased significantly. After the introduction of the synergistic system, the CO2 release of UPR-7, UPR-8 and UPR-9 also decreased compared with UPR-6.
[0065] like Figure 7 As shown in the figure, the CO release of pure sample UPR-0 is the highest. After adding the phosphorus flame retardant APP, the CO release begins to decrease. After the introduction of the synergistic system, the carbon monoxide release further decreases. The cross-linked montmorillonite with super acid structure can better prevent the leakage of toxic gases than Na-MMT, so the release of carbon monoxide and carbon dioxide has decreased.
[0066] like Figure 8 As shown in the figure, the total smoke release of pure sample UPR-0 is the lowest. After adding phosphorus flame retardant APP, the total smoke release of UPR-6 increases significantly. This is because phosphorus-containing flame retardants will release a large amount of smoke when burning, which is harmful to the human body and the environment. Fig. 9 As shown, the smoke release rate of UPR-6 is slightly higher than that of pure UPR. After the introduction of the synergistic system, the presence of the flakes will prevent the release of smoke, so the total amount of smoke released is reduced and the smoke release rate is also reduced. The cross-linked montmorillonite with a super acid structure has a lower total amount of smoke release and smoke release rate than Na-MMT, so the smoke suppression performance is also better.
[0067] like Fig.10 and Fig.11 As shown in the figure, after combustion, the total amount of heat released (THR) and the heat release rate (HRR) of the pure UPR sample reached the highest level. After adding the flame retardant APP, the THR and HRR of sample UPR-6 decreased significantly, indicating that the addition of flame retardant has a good effect on the reduction of sample THR and HRR. After the introduction of the synergistic system, the THR and HRR of UPR-7, UPR-8 and UPR-9 further decreased, and the THR and HRR of UPR-8 and UPR-9 were lower than those of UPR-7. This shows that the synergistic flame retardant is better than that of only adding flame retardants, and the cross-linked montmorillonite with a super acid structure has a more significant effect on reducing the sample THR and HRR than the original Na-MMT.
[0068] like Fig.12 and 13 As shown in the figure, compared with the pure sample UPR-0, the thermogravimetric curves of other samples UPR-6, UPR-7, UPR-8 and UPR-9 have basically the same downward trend, and the mass loss rate is also similar. After adding the phosphorus-containing flame retardant APP, the loss in the first stage is less than that of the pure sample UPR-0, and the remaining mass is also more than that of the pure sample UPR-0. After adding Na-MMT, TiO2 / SO4 2- -PILCs and ZrO2 / SO4 2- After the PILCs form a synergistic system, the thermal stability is further improved and the weight loss rate is also reduced. It is not difficult to see from the curve that TiO2 / SO4 2— -PILCs and ZrO2 / SO4 2- -PILCs have better thermal stability than Na-MMT. After Ti-PILCs and Zr-PILCs are calcined in a muffle furnace, the hydrated ions between their layers are transformed into dehydrated oxidized columns, and chemical bonds are generated between the crystal layers, which makes their structure have good thermal stability.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A flame retardant montmorillonite solid superacid, characterized in that: The montmorillonite skeleton and interlayer are used as cages to encapsulate and anchor the super acid ligand, wherein the super acid ligand is a metal atom M, and a MO-Si bond is formed between the metal atom M and the montmorillonite skeleton or interlayer. The metal atom M also binds to SO4 2- Through SOM bond coordination, a B acid center is formed.
2. The flame retardant montmorillonite solid superacid according to claim 1, characterized in that: The metal atom M is Ti, Zr, Sn or Fe.
3. The method for preparing the flame-retardant montmorillonite solid superacid according to claim 1 or 2, characterized in that: The following steps are involved: (1) calcining the metal ion cross-linked montmorillonite at 700-900° C. for 1-3 h to obtain metal atom pillared montmorillonite; (2) immersing the metal atom pillared montmorillonite in a sulfuric acid solution, allowing it to stand, filtering and drying it, to obtain a dried product; (3) calcining the dried product at 400-600° C. for 3-5 h to obtain montmorillonite solid superacid.
4. The preparation method according to claim 3, characterized in that: The metal ion cross-linked montmorillonite in step (1) is titanium cross-linked montmorillonite, zirconium cross-linked montmorillonite, tin cross-linked montmorillonite or iron cross-linked montmorillonite.
5. The preparation method according to claim 4, characterized in that: The preparation method of titanium cross-linked montmorillonite is as follows: under stirring conditions, 5-7 ml of Ti(C4H9O)4 is added dropwise to 3-5 ml of concentrated hydrochloric acid, and the mixture is stirred for 20-40 minutes, and then the mixture is allowed to stand at room temperature for 2-4 hours under sealed conditions to obtain a titanium cross-linking agent; Under stirring conditions, a titanium crosslinking agent is added to a sodium-based montmorillonite suspension, and the mixture is stirred for reaction for 2-4 hours. After standing, the mixture is centrifuged, filtered, dried, and ground to obtain titanium crosslinked montmorillonite.
6. The preparation method according to claim 4, characterized in that: The preparation method of zirconium cross-linked montmorillonite is as follows: 0.5-1.5 ml of concentrated hydrochloric acid, 35-40 ml of distilled water and 1-2 g of ZrOCl2 powder are mixed, magnetically stirred for 20-40 minutes, and allowed to stand for 2-4 hours to obtain a zirconium cross-linking agent; The zirconium crosslinking agent is added to the sodium montmorillonite suspension, stirred for reaction for 2-4 hours, allowed to stand overnight, centrifuged, filtered, dried, ground, and finally calcined at 450-550° C. for 2-4 hours to obtain zirconium crosslinked montmorillonite.
7. The preparation method according to claim 5 or 6, characterized in that: The preparation method of the sodium-montmorillonite suspension is as follows: 1 g of sodium-montmorillonite, 100 ml of acetone and 40 ml of deionized water are mixed to obtain the sodium-montmorillonite suspension.
8. The preparation method according to claim 3, characterized in that: In step (2), the concentration of the sulfuric acid solution is 1 mol / L, and the solvent of the sulfuric acid solution is water.
9. The preparation method according to claims 5 and 6, characterized in that: The mass percentage of concentrated hydrochloric acid is 36-37%.
Citation Information
Patent Citations
A kind of hydrolysis catalyst and preparation method thereof and method for preparing succinaldehyde
CN105457684B
Preparation method of two-dimensional solid superacid, two-dimensional solid superacid and application of two-dimensional solid superacid
CN116020425A
